2019
DOI: 10.18280/acsm.430507
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Tribological Properties of Chloride-Based and Tetra Fluoroborate-Based Ionic Liquids

Abstract: Methyl-imidazolium based ionic liquids have good tribological properties, because of their ability to form a chemically reacted film on the surface. This paper mainly compares the tribological properties of two ionic liquids, namely, the chloride-based imidazolium ionic liquid (IL1) and the tetrafluoroborate-based methyl-imidazolium ionic liquid (IL2). The two ionic liquids were synthesized in the lab and blended with mineral base oil at various proportions, i.e. 0.5 %, 1 % and 1.5 % by weight. The tribologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The samples were prepared by using a graphite crucible and a stainless steel permanent mould. Optical microscopy technique was employed to observe the particle distribution in the composite [21]. The results of the investigation showed that increase in the hardness of the aluminium metal matrix was due to the addition of AlN (aluminium nitride) as reinforcement particles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The samples were prepared by using a graphite crucible and a stainless steel permanent mould. Optical microscopy technique was employed to observe the particle distribution in the composite [21]. The results of the investigation showed that increase in the hardness of the aluminium metal matrix was due to the addition of AlN (aluminium nitride) as reinforcement particles.…”
Section: Literature Reviewmentioning
confidence: 99%